Design of Mobile Scooter to Increase Flexibility and User Friendliness - Goh, Zong Wei; Nik Hisyamudin Muhd Nor, (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Mobile scooter is a light-weight transportation device that is specially designed for short distance travel. Due to the size and less flexibility characteristic of existing product in the market, the mobile scooter is not easy to be store and carry. Hence, the objective of this project is to design a flexible and user-friendly mobile scooter that can be carried easily. The general idea of the mobile scooter is typically based on customer’s expectation and requirement. The design process method introduced by George E. Dieter is referred to as the guideline of this project including conceptual design, embodiment design and detail design. The analysis by formula calculation and SolidWorks software are done to ensure the specification and quality of mobile scooter reach the customer requirement. The final design expected to be more flexible and user friendly. The power rating of mobile scooter is 500W with maximum speed of 25km/hr. The dimension of mobile scooter before folding is 1124mm(L) x 464mm (W) x 1200mm(H) and the height reduce to 360mm after folded. The estimated weight of mobile scooter is 12.8kg including motor and battery. The objective had been achieved in aspect of flexibility and user friendliness.